I CAN intervention to increase grit and growth mindset: exploring the intervention for 15-year-olds Norwegian adolescents - Sigmundsson, Hermundur; Hauge, Håvard; Leversen, Jonas S. R.; Haga, Monika (Frontiers in Education, 2024)
The purpose of the current study was to examine the effects of a 2 × 45 min intervention to increase the beliefs of ‘I CAN’. Four hundred and twenty-one 15-year-old students participated in this study. The participants were selected from 38 schools in Norway which carried out the program MOT. The adolescents were randomly selected to either an experimental group or control group. Both groups carried out an intervention program that was completely new for them. The experimental group carried out the new I CAN intervention and the control group carried out an intervention with focus on parts of the brain. The participants completed a pre-test assessment of the Grit-S Scale and Growth Mindset scale. This was followed up by the novel intervention I CAN for 256 of the participants (experimental group) and control intervention for 165 of the participants. The results showed a significant increase in Grit for the males in the experimental group. Our aim was to create an intervention where the participants would “turn on the switch,” meaning that they develop stronger beliefs, i.e., changing beliefs. The results indicate that we may have been successful. These promising results are now being following up on high school students, age 16–19, in Norway.